An insight into clinical trials: Perspectives and practices - Wiktoria Wisniewska, Sara Alnasir Kassam, Dilruba Boksh, Mahesh Nirmalan, Jonathan Bannard-Smith (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Issue 6 Co-Editors-in-Chief Wiktoria Wisniewska and Sara Alnasir Kassam had the pleasure of having a conversation with Dr Jonathan Bannard-Smith and Professor Mahesh Nirmalan regarding Clinical Trials and their importance in developing lifesaving treatments and answering clinical questions. Dr Jonathan Bannard-Smith is a Critical Care & Anaesthesia Consultant at Manchester University NHS Foundation Trust. Professor Mahesh Nirmalan is a medical education professor, an Honorary Critical Care Medicine Consultant at Manchester Royal Infirmary, and Former Vice Dean for social responsibility at the University of Manchester.
Keywords: clinical trials; evidence-based medicine; ethical protocols; patient outcomes; informed consent; risk-benefit balance; data protection; placebo; inclusion criteria; patient-centred research; digital security